2008
DOI: 10.1002/ccd.21406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medical treatment and coronary revascularization in patients with moderate coronary lesions and borderline fractional flow reserve measurements

Abstract: In patients with moderate coronary lesions and borderline FFR measurements deferral of revascularization was associated with a higher rate of MACE (CR) and a higher prevalence of angina at follow-up, especially in those with previous MI in the territory evaluated by FFR. Further prospective randomized studies should confirm whether or not an FFR cut-off point of 0.80 instead of 0.75 would be more appropriate for deferring CR in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
3
36
1
Order By: Relevance
“…Our findings differ from those in the study by Courtis et al, 23 who observed in 107 patients that deferral of revascularization in patients who had moderate coronary lesions and FFR measurements in the borderline range between 0.75 and 0.80 was associated with a higher rate of cardiac events after 1 year. These were largely attributed to a significantly higher rate of coronary revascularizations in the target vessel due to the persistence or increase in angina symptoms.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings differ from those in the study by Courtis et al, 23 who observed in 107 patients that deferral of revascularization in patients who had moderate coronary lesions and FFR measurements in the borderline range between 0.75 and 0.80 was associated with a higher rate of cardiac events after 1 year. These were largely attributed to a significantly higher rate of coronary revascularizations in the target vessel due to the persistence or increase in angina symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…We conclude from our study as well as from the data of Courtis et al 23 and Lavi et al, 26 that patients with borderline FFR measurement values may be deferred from revascularization without putting them at an increased risk for ''hard'' events, such as MI and cardiac death. It therefore seems reasonable to recommend medical treatment and continued surveillance for the majority of these patients as a first line therapy.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…When precatheterization stress testing is not available or is thought to underestimate the severity of coronary disease, physiologic testing with FFR may be helpful. An FFR of <0.75 correlates well with ischemia on stress testing [40,42,[47][48][49][50]. For patients with an FFR between 0.75 and 0.80, angina at follow-up was less prevalent in those who underwent PCI compared with those treated conservatively [50].…”
Section: Methods Of Determining Significance Of Coronary Diseasementioning
confidence: 99%
“…An FFR of <0.75 correlates well with ischemia on stress testing [40,42,[47][48][49][50]. For patients with an FFR between 0.75 and 0.80, angina at follow-up was less prevalent in those who underwent PCI compared with those treated conservatively [50]. An FFR of >0.75 or >0.80 correlates with excellent long-term outcomes if PCI is deferred [40,43,[51][52][53].…”
Section: Methods Of Determining Significance Of Coronary Diseasementioning
confidence: 99%